Catalytic oxidation of volatile organic compounds by non-noble metal catalyst: Current advancement and future prospectives. (20th August 2022) - Lou, Benzhen; Shakoor, Noman; Adeel, Muhammad; Zhang, Peng; Huang, Lili; Zhao, Yongwen; Zhao, Weichen; Jiang, Yaqi; Rui, Yukui
Abstract: Since the inception of urbanization and industrialization, emissions of volatile organic compounds (VOCs) have become serious concern due to harmful effects on terrestrial biota, serious measures must be taken to minimize the emissions of VOCs. Catalytic oxidation is considered one of the most promising technologies for removing VOCs for its low ignition temperature, high efficiency, and no secondary pollution in the process of treatment. This review summarizes progress made in the catalytic oxidation of VOCs over last ten years. We have discussed the mechanism and current advancement of non-noble metal catalysts to remove VOCs. Besides, the characteristics and the factors affecting catalytic performance of non-noble metal catalysts are comprehensively explained. The critical factors that affect the catalytic performance of catalysts mainly include preparation methods, modification technologies, and carrier materials. Therefore, future research should focus on developing efficient catalysts and performance improvement. We believe that current review will provide a great foundation and reference point for future design and development in this field. Graphical abstract: Image 1